Stylised facts of the business cycle in Barbados - Maurin, Alain ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Examines the characteristics of the business cycle in Barbados for the quarterly period 1974-2003 using several adoptive and non-adoptive filters. Describes and explains the business cycle and predicts the dynamic linkages among principal macroeconomic variables.